A minimal constraint device for imaging nuclei in live Drosophila contractile larval muscles reveals novel nuclear mechanical dynamics. Issue 12 (20th May 2020) - Lorber, Dana; Rotkopf, Ron; Volk, Talila
Abstract : Muscle contractions produce reiterated cytoplasmic mechanical variations, which potentially influence nuclear mechanotransduction, however information regarding the dynamics of muscle nuclei in the course of muscle contraction is still missing. Abstract : Muscle contractions produce reiterated cytoplasmic mechanical variations, which potentially influence nuclear mechanotransduction, however information regarding the dynamics of muscle nuclei (myonuclei) in the course of muscle contraction is still missing. Towards that end, a minimal constraint device was designed in which intact live Drosophila larva is imaged, while its muscles still contract. The device is placed under spinning disc confocal microscope enabling imaging of fluorescently labeled sarcomeres and nuclei during muscle contraction, without any external stimulation. As a proof of principle we studied myonuclei dynamics in wild-type, as well as in Nesprin/klar mutant larvae lacking proper nuclear–cytoskeletal connections. Myonuclei in control larvae exhibited comparable dynamics in the course of multiple contractile events, independent of their position along the muscle fiber. In contrast, myonuclei of mutant larvae displayed differential dynamics at distinct positions along individual myofibers. Moreover, we identified a linear link between myonuclear volume and its acceleration values during muscle contraction which, in Nesprin/klar mutants exhibited an opposite tendency relative to control. Estimation of the drag force applied on individual myonuclei revealed that force fluctuations in time, but not the average force, differed significantly between control and Nesprin/klar mutant, and were considerably higher in the mutant myonuclei. Taken together these results imply significant alterations in the mechanical dynamics of individual myonuclei in the Nesprin / klar myonuclei relative to control. Such differences provide novel mechanical insight into Nesprin function in contractile muscles, and might reveal the mechanical basis underlying Nesprin -related human diseases.